Inherited factors in pre-eclampsia: Molecular genetic and epidemiological studies in a Sri Lankan population - Dissanayake, Vajira Harshadeva Weerabaddana (2004)
Pre-eclampsia is a disorder of unknown aetiology that affects about 5% of Sri Lankan women during their pregnancy. It is most likely a multifactorial disorder that is caused by the interaction of genetic and environmental factors. Recent advances in genetics have resulted in a surge of investigations into genetic factors underlying pre-eclampsia. These studies have been conducted mainly in the white Caucasians in the West and the Japanese in the East.